2017
DOI: 10.1016/j.ajme.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant, hypoglycemic and oral glucose tolerance test of banana peels

Abstract: Banana fruit is claimed to have antidiabetic effects despite its high calorie content, and its peels also contain vital phytoconstituents including gallocatechin. Previously banana pulp has been studied for antihyperglycemic effects, and in the present investigation antihyperglycemic effect of ethanolic extract of inner peels of Musa sapientum (EMS), Musa paradisiaca (EMP), Musa cavendish (EMC) and Musa acuminata (EMA) fruit was evaluated using oral glucose tolerance test in normoglycemic rats. In vitro antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Donating electron to reduce ferric ion to ferrous ion and Mo (VI) to Mo (V) is an indication of reducing power. The reducing capacity of a compound may be directly translated as an indicator of antioxidant activity [14]. The strong reducing power of N. latifolia ethanolic leaf extract might be as a result of its phenolic content, as they are good electron donors [15].…”
Section: Resultsmentioning
confidence: 99%
“…Donating electron to reduce ferric ion to ferrous ion and Mo (VI) to Mo (V) is an indication of reducing power. The reducing capacity of a compound may be directly translated as an indicator of antioxidant activity [14]. The strong reducing power of N. latifolia ethanolic leaf extract might be as a result of its phenolic content, as they are good electron donors [15].…”
Section: Resultsmentioning
confidence: 99%
“…In ferric reducing power and H 2 O 2 scavenging assay, Musa acuminata also showed best antioxidant activity when compared with other extracts. The study revealed that the peels of Musa species possess significant in vitro antioxidant activity, hence, the conclusion that eating the peel of banana fruit would be beneficial considering its potential antioxidant property [24]. It was also reported that ethanol extracts of unripe Cavendish (Musa acuminata L) and Dream banana (Musa acuminata colla.…”
Section: Antioxidant Activitymentioning
confidence: 95%
“…High level of glucose is prominent in diabetic patients and attempts have been made to counteract that using several plants including banana. Investigation into the anti-hyperglycemic effect of ethanol extract of Musa sapientum (EMS), M. paradisiaca (EMP), Musa cavendish (EMC), and M. acuminata (EMA) peels by oral glucose tolerance test in glucose-loaded (2 g/kg p.o) normoglycemic (having normal concentration of glucose) rats was done by [24]. It was observed from this study that animals treated with EMC (500 and 1000 mg/ kg, p.o) and EMA (200 and 400 mg/kg p.o) showed marked anti-hyperglycemic effect (p < 0.01).…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…Ethanolic extract of banana peels at 500 mg/kg exhibited minor reduction of blood glucose in normal rats compared to normal, 120 min after extract administration. Also, the same dose showed antihyperglycemic effects compared to normal during OGTT and from 90 min (Navghare and Dhawale, 2017) Hepatoprotective, Antioxidant (Swathi et al, 2011) Myrtaceae: Psidium guajava L. (Mathur et al, 2015).…”
Section: Fromage Barks Leaves Rootsmentioning
confidence: 99%